Infectious Forest Diseases 2013
DOI: 10.1079/9781780640402.0436
|View full text |Cite
|
Sign up to set email alerts
|

Dothistroma needle blight.

Abstract: This chapter focuses on the epidemiology and management of Dothistroma needle blight (DNB), which is one of the most important foliar diseases of pines (Pinus spp.) worldwide, caused by D. septosporum and D. pini (Mycosphaerella pini). Information is given on the pathogen distribution, host range, detection and infection biology, as well as management strategies and tactics, which include avoidance, exclusion, eradication, protection (using fungicides and biological control agents), genetic resistance, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 0 publications
2
70
0
3
Order By: Relevance
“…Of these dothistroma needle blight caused by Dothistroma septosporum (Doroguine) Morelet (Bulman et al 2013), cyclaneusma needle cast caused by Cyclaneusma minus (Butin) Di Cosmo, Peredo & Minter (Gadgil 1984) and the wood wasp Sirex noctilio Fabricius ) have caused damage to forests at some periods and in some locations in New Zealand. Each of these pests is now subject to active management, so resulting productivity losses are generally at acceptably low levels Bulman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Of these dothistroma needle blight caused by Dothistroma septosporum (Doroguine) Morelet (Bulman et al 2013), cyclaneusma needle cast caused by Cyclaneusma minus (Butin) Di Cosmo, Peredo & Minter (Gadgil 1984) and the wood wasp Sirex noctilio Fabricius ) have caused damage to forests at some periods and in some locations in New Zealand. Each of these pests is now subject to active management, so resulting productivity losses are generally at acceptably low levels Bulman et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A group of Australian foresters who visited New Zealand in December 1965 observed that P. radiata at 2000 to 4000 stems ha -1 at 15 years of age was heavily diseased, but a nearby area with much lower stocking was uninfected (Marks 1966). Reducing stand density by planting at a lower initial stocking, along with thinning, has been shown to reduce disease levels in several studies in Australia (Marks and Smith 1987;Marks et al 1989;Neumann et al 1993), Chile (Alzamora et al 2004), Kenya ), New Zealand (Van der Pas 1984Bulman et al 2013) and the USA (Van Haverbeke and Boldt 1968).…”
Section: Silvicultural Management -Thinningmentioning
confidence: 99%
“…Decades of field observations from a number of countries have determined that disease levels tend to be high in gullies and low-lying areas where trees remain wet for prolonged periods (Marks et al 1989;Bulman et al, 2004;Brown and Webber 2008;Crisan et al 2015). The same effect is often seen where low clouds, or fog, sits on ridge tops.…”
Section: Factors Contributing To Disease Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Dothistroma needle blight, caused by the fungal pathogens Dothistroma septosporum and D. pini, is a major disease of Pinus spp. worldwide (Bulman et al 2013). In many areas, there have been significant increases in outbreak frequency and the disease has recently expanded into new areas (Barnes et al 2008).…”
Section: Forest Health Impacts Under Future Climatementioning
confidence: 99%